2023
DOI: 10.1111/nph.19331
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of GoPGF reveals that the pigment glands are synthetic sites of gossypol in aerial parts of cotton

Zhen‐Nan Zhang,
Lu Long,
Xiao‐Tong Zhao
et al.

Abstract: Summary Gossypol and the related terpenoids are stored in the pigment gland to protect cotton plants from biotic stresses, but little is known about the synthetic sites of these metabolites. Here, we showed that GoPGF, a key gene regulating gland formation, was expressed in gland cells and roots. The chromatin immunoprecipitation sequencing (ChIP‐seq) analysis demonstrated that GoPGF targets GhJUB1 to regulate gland morphogenesis. RNA‐sequencing (RNA‐seq) showed high accumulation of gossypol biosynthetic genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…To analyze the relationship between GhHAM and GoPGF, we measured the expression of GhHAM and GoPGF in both gopgf (Zhang et al., 2024) and ghham mutants. As shown in Figure 4, the expression of GoPGF in the leaves, stems, and carpel walls of the gopgf mutants was dramatically reduced compared to the WT, possibly due to the lack of gland structure in gopgf .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To analyze the relationship between GhHAM and GoPGF, we measured the expression of GhHAM and GoPGF in both gopgf (Zhang et al., 2024) and ghham mutants. As shown in Figure 4, the expression of GoPGF in the leaves, stems, and carpel walls of the gopgf mutants was dramatically reduced compared to the WT, possibly due to the lack of gland structure in gopgf .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that terpenoids can inhibit the growth of pathogens and pests (Gao et al., 2013; Sharma et al., 2017; Tian et al., 2015). The presence of a large amount of terpenoids strongly suggests that terpenoid‐synthesizing glands in plants are evolutionarily considered an effective defense mechanism against adverse environments (Cheng et al., 2007; Zhang et al., 2024). In cotton breeding, the gossypol content is often evaluated as an indicator of the cotton's ability to defend itself against pests, although the specific role of the pigment glands remains to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the MpERF13 gene is required for oil body formation and terpenoid biosynthesis in M. polymorpha ( 36 ). Overall, CsMYC5 plays a role in promoting a secondary metabolism similar to that of its closest cotton homolog GoPGF, but its involvement in gland development was restricted to later stages unlike GoPGF, which controls the initiation of glandular trichomes ( 37 , 38 ). This observation suggests that distinct developmental programs are involved in governing secretory cavity formation and glandular trichome initiation.…”
Section: Discussionmentioning
confidence: 99%